Rancang Bangun Aplikasi Pengelolaan Barang Pada Divisi Gudang PT. Krian Indah Jaya - Ernanto, Nikolas Baru; Sulistiowati, Sulistiowati; Nurcahyawati, Vivine (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
The process of Goods management process that includes record incoming goods, recorded goods out and the procurement of goods on division of goods PT. Krian Indah not computerized. The existing problems which is the first the manufacture of a report still comparing data recording goods in and freight out. The second is the in preparing event that is to be held had difficulty to the required because data statement goods late submitted. The third is The incompatibility the number of an inventory of goods who recorded with the amount of goods that is in a warehouse. Fourth is Demand goods by division who runs the event still use the small notes so easy to missing. The A solution to solve the problem is application that can be records the transactions of goods in and freight out. So that transactions goods in and freight out can regular. System can figure out the points order repeated goods ( reorder point ) that would give information a time warning and the number of order repeated goods. System can also pathetic form demand goods substitute notes small that division goods although the data shaped archive also has data on a database .Based on the results of the tryouts that has been done , this system able to meet a need to division warehouse pt .Krian beautiful jaya in management process of goods , the preparation of reports on goods , stocks report , report rop goods . Keywords: Goods Management, Reorder Point, Web Based Application.